Reingeniería de la Evaluación de Programas de Formación - Bernardo MARTÍNEZ MUT (Teoría de la Educación: Revista Interuniversitaria, 2009)
The programmes evaluation acquières special relevance because of the social and economic dimensions of their outcomes. But it is difficult to defend that the programmes have been applied and evaluated in the same way they were planned. Therefore it es necessary to solve the question of the programmes evaluability, since it is imposible to attribute the out-comes to the activities without accomplishing several conditions or requirements; these are the conditions for the success of the programmes, which facilitate the integration between the planification and evaluation functions. We present two experiences about educative programmes in company that pretend to show the application of those conditions. The reengineering, as a strategy of radical improving of the processes, allows to re-design the evaluation and the planification functions of the programme.